Metallapentalenofurans and Lactone‐Fused Metallapentalynes. Issue 26 (7th April 2017) - Lu, Zhengyu; Zhu, Congqing; Cai, Yuanting; Zhu, Jun; Hua, Yuhui; Chen, Zhixin; Chen, Jiangxi; Xia, Haiping
Abstract: Metalla‐aromatics are attractive species because they exhibit the properties of both organometallics and aromatics. Reported metal‐bridged polycyclic aromatic complexes, as well as Möbius aromatic species, are still rare. Herein, we present the construction of two new metal‐bridged polycyclic aromatic frameworks, α‐metallapentalenofurans and lactone‐fused metallapentalynes, by the reactions of osmapentalyne with terminal aryl alkynes in the presence of H2 O or HBF4 /H2 O, respectively. DFT calculations show that the α‐metallapentalenofurans possess rare planar Craig‐type Möbius aromaticity derived from the 11‐center‐12‐electron dπ –pπ π‐conjugation. This study offers a new route for the construction of polycyclic metalla‐aromatics as well as planar Möbius aromatic species. Abstract : Metal in the roof : The first α‐metallapentalenofurans and lactone‐fused metallapentalynes were constructed by the reactions of metallapentalyne with aryl alkynes under different conditions. DFT calculations reveal that this novel metallapentalenofuran framework exhibits Möbius aromaticity derived from the 11‐center‐12‐electron dπ –pπ π‐conjugation.